The ageing of people living with cystic fibrosis: what to expect now? - Almudena Felipe Montiel; Antonio Álvarez Fernández; Mario Culebras Amigo; Letizia Traversi; David Clofent Alarcón; Karina Loor Reyes; Eva Polverino (European Respiratory Review)
The prognosis of people with cystic fibrosis (pwCF) has improved dramatically with the introduction of cystic fibrosis transmembrane conductance regulator (CFTR) modulators (CFTRm). The ageing of the cystic fibrosis (CF) population is changing the disease landscape with the emergence of different needs and increasing comorbidities related to both age and long-term exposure to multiple treatments including CFTRm. Although the number of pwCF eligible for this treatment is expected to increase, major disparities in care and outcomes still exist in this population. Moreover, the long-term impact of the use of CFTRm is still partly unknown due to the current short follow-up and experience with their use, thus generating some uncertainties. The future spread and initiation of these drugs at an earlier stage of the disease is expected to reduce the systemic burden of systemic inflammation and its consequences on health. However, the prolonged life expectancy is accompanied by an increasing burden of age-related comorbidities, especially in the context of chronic disease. The clinical manifestations of the comorbidities directly or indirectly associated with CFTR dysfunction are changing, along with the disease dynamics and outcomes. Current protocols used to monitor slow disease progression will need continuous updates, including the composition of the multidisciplinary team for CF care, with a greater focus on the needs of the adult population.